A Brief Study and An Arduino Based Implementation of Booth’s Multiplication Algorithm - Ghosh, Kushankur; Banerjee, Arghasree (International Journal of Computer Sciences and Engineering, 2019)
The main objective behind this paper was to provide a brief overview about some of the well-known multiplication algorithms and design an Arduino based calculator working on the principles of the Booth’s multiplication Algorithm in the simplest and cheapest possible way. Our study surrounds some of the algorithms that existed before and around the time when Booth’s multiplication Algorithm came into the scene. The study found that each of the algorithms had some problems which ultimately galvanized the popularity of the Algorithm proposed by Arnold Donald Booth. The calculator we designed is capable of taking a four-bit binary multiplier and a four-bit binary multiplicand as input and will produce the product in an eight-bit sequence as the output. The calculator is basically constructed with the help of a central controlling Arduino connected to various input and output specified electronic components such as push buttons and LEDs. The circuit constructed to perform the algorithm is the simplest possible circuit. The input to the Arduino can be given from the hardware itself and the output also gets reflected through the hardware.